Society and climate transformations and challenges - Stehr, Nico.; Machin, Amanda (Singapore : World Scientific Publishing, 2019)
Climate has for a long time been a taken-for-granted background against which social, political and economic interactions have taken place. But this taken-for-granted background is cleaving. It is becoming hard to ignore the potential repercussions of a changing climate, and the uneven impact of certain forms of human society and energy cultures that risk undermining their own environmental conditions. In a comprehensive and accessible way, this book provides a broad account of the various conceptions and constructions of climate and its shifting interconnections with society, science and politics; incorporates both natural and social scientific perspectives; and situates contemporary climate change research in an historical context. Drawing on the insights of various disciplines and citing numerous examples, Society and Climate probes the interplay between society, science and climate, and warns against making any easy assumptions.
Introduction: society, nature, climate. The nature of weather ; The climate of science ; The climate of society ; Conclusion: Climates of disagreement -- Climate as scientific object. Climate as average weather ; Measuring the climate ; The emergence of a new paradigm ; The discovery of the "greenhouse effect" ; Modelling the climate ; Conclusion: Climate as possible weather -- Climate as cycle and change. The history of the science of climate change ; Natural climate variability ; Anthropogenic climate change ; Measuring and modelling climate change ; The impact and inequality of climate change ; Conclusion: Understanding change -- Climate as determinant. Climate works? ; Ellsworth Huntington ; Climate determinism: a critique ; Climate determinism: a revival? ; Climate determinism: a comparison ; Conclusion: Climate matters -- Climate as public perception. Trusting the climate ; Distrusting the climate? ; Mistrusting the science? ; Conclusion: Social change? -- Climate as policy issue. Scientific policy ; Economic policy ; Regulatory policy ; Climate policy: who decides? -- Summary and prospects.
Mode of access: World Wide Web.
Includes bibliographical references and indexes.
Keywords: Climatic changes -- Social aspects; Climatic changes -- Political aspects; Climatic changes -- Economic aspects; Climatic changes -- Effect of human beings on; Electronic books